PENERAPAN NILAI-NILAI PENDIDIKAN KARAKTER DALAM SURAT ALI-IMRON AYAT 102-104 SISWA KELAS 12 PONDOK PESANTREN TAHFIZHUL QUR'AN QORYATUL QUR'AN WERU SUKOHARJO TAHUN AJARAN 2024/2025 - Ambia, Roby Nur; Rochmawan, Alfian Eko; Baehaqi, B (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This study examines the implementation of character education values in QS. Ali Imran verses 102-104 among 12th-grade students at PPTQ Qoryatul Qur’an Weru Sukoharjo. The research aims to explore the application of Qur’anic character education values and identify supporting and inhibiting factors. A qualitative approach was used, with data collected through interviews, observations, and documentation. The findings indicate that values such as obedience, maintaining good conduct, avoiding division, fostering brotherhood, and caring for others are applied through the halaqah learning method in classrooms and mosques. Key supporting factors include teacher support, a conducive pesantren environment, and adequate facilities, while inhibiting factors consist of time constraints, student environment, and moral decline. This study confirms that Qur’anic-based character education has a positive impact on shaping students' ethics and attitudes.